The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12889-020-08483-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sleep problems on daytime function in school life: a cross-sectional study involving Japanese university students

Abstract: Background: The aims of this study were 1) to clarify the prevalence of sleep problems (insomnia, insufficient sleep, and delayed sleep-wake phase) among Japanese university students; 2) to examine sociodemographic characteristics, lifestyle, and sleep-related symptoms in each sleep problem; and 3) to evaluate the association between the above-mentioned sleep problems and daytime dysfunction in school life. Methods: Self-report questionnaire surveys were conducted at eight universities in Japan, and we receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 52 publications
3
16
0
4
Order By: Relevance
“…The incidence of sleep disorder in the present study is similar to that in a previous study that demonstrated sleep problems in Japanese university students [14]. Sleep disorder is de ned as PSQI-J ≥ 5.5.…”
Section: Subject Characteristicssupporting
confidence: 88%
“…The incidence of sleep disorder in the present study is similar to that in a previous study that demonstrated sleep problems in Japanese university students [14]. Sleep disorder is de ned as PSQI-J ≥ 5.5.…”
Section: Subject Characteristicssupporting
confidence: 88%
“…An evening chronotype in children of pre-scholar and scholar age revealed a higher association with several sleep disorders, but no specific association with parasomnia [77,78]. Conversely, an association between a delayed sleep-wake phase and the occurrence of NREM parasomnias was found among Japanese students [79].…”
Section: Circadian Rhythm and Chronotypementioning
confidence: 78%
“…We further investigated the influence of the changes in sleep–wake schedules on individual lifestyles and negative emotions, and found that the delayed sleep–wake times could positively predict the participants' negative emotions and electronic device use, but negatively predict the exercise levels during the stay‐at‐home orders. Previous literature had proved that sleep loss and late nocturnal sleep are related to deterioration in physical health, mental health and quality of life (Haraden et al., 2017; Kayaba et al., 2020; Krističević et al., 2018; Morita et al., 2015). Delayed sleep–wake patterns can negatively predict positive emotions and social experiences (Asaoka et al., 2004; Segura‐Jiménez et al., 2015; Totterdell et al., 1994).…”
Section: Discussionmentioning
confidence: 99%